Uso de la cascara de arroz como fuente de energía en la fabricación de ladrillos cerámicos de alta calidad en la provincia de lamas departamento de san martín - Yrupailla Montes, César Elmer (2010)
The production of briquettes was an urgent necessity to replace to the traditional fuels as the firewood, the coal and other fuels this way we avoid the indiscriminate pruning of the forests. In this project, recommendations are given, experiences in the study of the prosecution of the briquette of rice shell. The use of the briquette will be possible for industrial purposes for this action were carried out experiments of use of briquette of shell of rice, specifically for the local production of bricks it will include the use of the ashy ones of briquette of shell of rice in the factory process of bricks manufacturing with the purpose of a final disposition of the ashes, besides increasing the resistance of the bricks, when incorporating it to the matter, and the substitution of the firewood as fuel, what will contribute to the indiscriminate pruning that in San Martin forest takes place. Another additional benefit will be the elimination of the contamination caused for the burns of rice shell and accumulation of the same one or its residuals. Although this innovation, largely caressed by many people, reality has been made belatedly, already this here is a promise. The factory of briquettes is still a project pilot. The briquette machine at the moment that the project owns only processes 30 kilograms per hour, but there is a plan to increase the capacity to process to more than a thousand kilograms per hour. Once proven their viability and the grade of acceptance among the population, the factory will extend its production.